Pengaruh Komunikasi dan Komitmen Organisasi Terhadap Kinerja Pegawai Pada Kantor Bappeda Kabupaten Bima - Tri Agustiani; Jaenab; Muhammad Badar (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
This research aims to determine the influence of communication and organizational commitment on employee performance at the Bima Regency Bappeda Office. The research instrument used in this research was a Likert scale questionnaire. The population in this study was all employees of the Bima Regency BAPPEDA Office totaling 113 people consisting of 64 ASN, 12 honorary workers and 37 volunteer workers. The sample in this study was 64 employees with ASN status at the Bima Regency BAPPEDA Office. The sampling technique was carried out using the purposive sampling method. The consideration is that there are 64 employees with ASN status at the Bima Regency BAPPEDA Office. The data in this research were collected by means of observation, questionnaires and literature study, then the data obtained were analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression, multiple correlation coefficients, determination tests, t tests and f tests with SPSS version 26 assistance. The research results show that Communication and Organizational Commitment have a significant effect on Employee Performance at the Bima Regency BAPPEDA Office.